(untitled) - Ross, Catherine Sheldrick (New York, 2009)
Teaches you to understand the needs of public, academic and special library users across different virtual settings - email, text messaging, and social networking websites - as well as in traditional and face-to-face models of communication. This book includes exercises and examples to help you practice effective reference transactions.
Keywords: Reference services (Libraries),Dịch vụ tham khảo (Thư viện)